Development of Project-Based E-Module to Facilitate Student's Mathematics Collaboration and Communication in Boarding School - Aprilia, Vina Ananda; Effendi, Moh. Mahfud; Rosyadi, Alfiani Athma Putri (Kreano, Jurnal Matematika Kreatif-Inovatif, 2024)
Technological advances in mathematics education emphasise the importance of students having good mathematical collaboration and communication skills. However, the use of electronic-based teaching devices that support this is still rarely found, especially in Islamic boarding schools. This research aims to develop teaching materials in the form of project-based e-modules to facilitate junior high school students' mathematical collaboration and communication skills for use in mathematics learning. This type of research is developed using the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The subjects of this research were students in class VIII-A Al-Izzah IIBS Batu in the Islamic boarding school curriculum. Data collection techniques include unstructured observation and interviews. Data collection instruments used expert validation sheets, e-module reflection sheets, and post-tests. The development of this learning media has been proven to be valid and practical, with an average percentage of validity of 95.86% and practicality of 93.33%. Apart from that, Project-based e-modules can support students in communicating well so that collaboration is formed in teams that can respect differences of opinion and be responsible for their contributions. Based on the results obtained, the project-based e-module is valid and practical in facilitating Islamic boarding school students' mathematical collaboration and communication skills in mathematics learning statistics material. Kemajuan teknologi dalam pendidikan matematika menekankan pentingnya siswa memiliki keterampilan kolaborasi dan komunikasi matematis yang baik. Namun, penggunaan perangkat ajar berbasis elektronik yang mendukung hal ini masih jarang dijumpai khususnya pada pondok pesantren. Penelitian ini bertujuan untuk mengembangkan bahan ajar berupa e-modul berbasis proyek untuk memfasilitasi kemampuan kolaborasi dan komunikasi matematis siswa SMP untuk digunakan dalam pembelajaran matematika pada. Jenis penelitian ini adalah pengembangan menggunakan metode Research and Development (R&D) dengan model ADDIE (Analysis, Design, Development, Implementation, Evaluation). Subjek penelitian ini adalah siswa kelas VIII-A Al-Izzah IIBS Batu pada kurikulum pondok pesantren. Teknik pengumpulan data berupa observasi dan wawancara secara tidak terstruktur. Instrumen pengumpulan data menggunakan lembar validasi ahli, lembar refleksi e-modul, serta post-test. Pengembangan media pembelajaran ini terbukti valid dan praktis, dengan persentase rata-rata validitas 95,86% dan praktisitas 93,33%. Selain itu, e-modul berbasis proyek dapat mendukung siswa dalam berkomunikasi yang baik sehingga terbentuk kolaborasi dalam tim yang dapat menghargai perbedaan pendapat serta bertanggungjawab atas kontribusi mereka. Berdasarkan hasil yang diperoleh, maka e-modul berbasis proyek valid dan praktis dalam memfasilitasi kemampuan kolaborasi dan komunikasi matematis siswa pondok pesantren pada pembelajaran matematika materi statistika.